Model Pendidikan Karakter melalui Homestay di SDIT Cahaya Bangsa Semarang - Fihris (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2018)
This present study aims to describe a school activity called ‘homestay’ that is carried out at SDIT Cahaya Bangsa Semarang, Central Java to shape the students’ character. This activity is originally inspired by “Jika Aku Menjadi”, a reality show program, broadcasted by an Indonesian private television station. Homestay manages the students to stay at a landlord house for several days and do all activities there such as farming, gardening, selling goods, and other domestic business for training them to be an independent individual. Homestay can be categorized as a character education performing self-habituation and conditioning. They represent extracurricular activities to be integrated into the school curriculum. The self-habituation and conditioning attempt to build the students’ character, including their personality, which is environmentally shaped through their life experiences during the Homestay program. In this school activity, the students are expected to stay for three days and experience what the landlord does. In 24-hour domestic activities, they are supposed to demonstrate togetherness and help each other. As a result, the students may adapt with their new condition that is completely different from what they experience in reality.